The Influence of Emotional Intelligence on the Performance of Ridan Permai Village Officials - Saru Reza; Diany Mairiza; Mustafa Kamal (Global Sustainability Research Institute, 2024)
Introduction: This research aims to explore and analyze the influence of emotional intelligence on the performance of village officials in Ridan Permai. Emotional intelligence is measured through aspects such as emotion recognition, emotion management, self-motivation, empathy, and social skills. Methods: This research used a survey to collect data which was distributed directly to Ridan Permai village officials at random. This research used the Slovin approach in determining the sample size and obtained 60 respondents who could be used for research. The simple linear regression analysis method is used to test the research hypothesis, then to test the research instrument using product moment for validity testing and Cronbach alpha for reliability testing, while testing classical assumptions using normality, multicollinearity, and heteroscedasticity tests. Results: The results of this research show that emotional intelligence has a positive effect on the work of Ridan Permai village officials. Conclusion and suggestion: These findings can be the basis for developing training and coaching programs aimed at increasing the emotional intelligence of village officials, with the hope of improving the quality of services and management at the village level. The practical implications of this research can support policymakers and stakeholders in optimizing the role of Ridan Permai village officials by increasing their emotional intelligence.